Study of the Application of Inventory Valuation Methods in Private Companies in the City of Surabaya - Selfie Ari Martini; Diana Zuhro; Tjandra Wasesa; Sutini Sutini; Achmad Daengs GS (Sean Institute, 2026)
This study was prepared to provide an overview of the inventory valuation method that should be applied by CV. Indo Listrik. The object used in this research is CV. Indo Listrik, located at Pergudangan Mutiara Margomulyo Permai A-21. The results of the research show that CV. Indo Listrik has been calculating inventory value using the LIFO method, in which LIFO assumes that the remaining goods (ending inventory) come from the earliest purchases, while the prices of goods continue to increase. As a result, the LIFO method causes the inventory value presented in the financial statements (balance sheet) not to represent the recent cost level of inventory. Moreover, it is clear that the LIFO method is no longer permitted under either PSAK regulations or tax regulations. Several conclusions can be drawn: CV. Indo Listrik may use the Average inventory valuation method, because this method produces a middle value for the cost of goods sold and ending inventory, not too high and not too low. Under the Average method, whenever prices change, both the cost of goods sold and the cost of ending inventory remain up to date. Therefore, the inventory value in the financial statements produced by the Average method better represents the recent cost level of inventory. The Average method also complies with applicable PSAK and tax regulations.